Cooperative Key Generation For Data Dissemination in Cyber-Physical Systems - Li, Kai (2018)
Poster presented in Work in Progress Session, ACM/IEEE International Conference on Cyber-Physical Systems (ICCPS 2018). 10 to 13, Apr, 2018. Porto, Portugal.